The diabetic foot medical and surgical management - Veves, Aristidis; Giurini, John M.; LoGerfo, Frank W. (Contemporary diabetes, 2012)
In The Diabetic Foot: Medical and Surgical Management, 3rd Edition, a distinguished panel of clinicians provides a thorough update of the significant improvements in knowledge surrounding the pathogenesis of diabetic foot problems, as well as the optimal healthcare treatment for this debilitating condition.¡ The authors, many practicing at the famous Joslin-Beth Israel Deaconess Foot Center, again illuminate the successful new multidisciplinary approach now clearly required for the successful treatment of diabetic foot.¡ Drawing on the experiences of diabetologists, podiatrists, vascular surgeons, infectious disease specialists, orthotists, plastic and orthopedic surgeons, this invaluable third edition, so timely given the continued rise of diabetes and its complications, clearly describes established techniques known to be effective.¡ This updated edition blends new knowledge with the time-tested principles of diabetic foot management and will be of significant value to all physicians and researchers with an interest in a state-of-the-art understanding of diabetic foot